High cycle fatigue life estimation of materials processed by laser powder bed fusion. Issue 7 (6th February 2019) - Hovig, Even W.; Azar, Amin S.; Sunding, Martin F.; Andreassen, Erik; Sørby, Knut
Abstract: The fatigue life of metal components is known to depend on the surface topography. For components made by laser powder bed fusion, the roughness of the as‐built surfaces depends on the orientation of the component surface with respect to the build plate. Surface topographies of AlSi10Mg and Inconel 718 specimens built at 0° to 90° inclination, with 15° increments, were characterised by white light interferometry. Two methods for calculating the stress concentration factor using the surface roughness data are proposed, and the results of each approach are presented and compared. Moreover, a finite element model was developed, in order to analyse the stress field when subsurface porosity is present. The fatigue lifetime estimates suggest that the lifetime of components may differ up to two orders of magnitude, depending on the build orientation.